FINDING A BALANCE BETWEEN INTELLECTUAL AND SPIRITUAL INTELLIGENCE IN THE MODERN ERA ACCORDING TO IBN KHALDUN - Farghita, Vania Salsabila (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
Abstract: This research aims to understand how to achieve a balance between intellectual and spiritual intelligence in modern times based on Ibn Khaldun's views. The main question asked was how Ibn Khaldun viewed the relationship between intellectual and spiritual intelligence in education. The research method involves an analysis of Ibn Khaldun's major works, especially the book "Muqaddimah", as well as a review of related literature that discusses his views on education and intellectual and spiritual development. The theory underlying this research is the holistic education concept of Ibn Khaldun, which unites religious and general knowledge. According to Ibn Khaldun, education not only functions to transfer knowledge, but also to shape the character and morals of students. He emphasized that education must include intellectual and spiritual aspects to create balanced and cultured individuals. In his view, religious science and general science should be taught together, because they are complementary and important for the development of a whole human being. The results of the study show that Ibn Khaldun emphasized the importance of developing students' overall potential by combining science and religion. He believes that holistic education will shape a cultured and moral society. This research has important implications for education in the modern era, especially in understanding the balanced relationship between intellectual and spiritual intelligence.